PERBANDINGAN PREDIKSI HARGA EMAS PER TROY ONS KURS DOLLAR AMERIKA SERIKAT PADA PERIODE TERTENTU MENGGUNAKAN ALGORITMA EXTREME GRADIENT BOOSTING - Putu Vikola Raditya (2023)
Computer technology has become an integral part of human life, with investors and traders utilizing this technology as a tool to analyze price movements in the capital markets. To predict the price of gold per troy ounce in relation to the US Dollar exchange rate, the method used is Extreme Gradient Boosting (XGBoost), an extension of Random Forest. This research expands the analysis by combining several common technical indicators used in analyzing gold price movements. By adding these technical indicators, prediction accuracy can be enhanced, although there will still be varying levels of errors depending on the processed data. This study utilizes a dataset of gold prices that is highly sensitive to other factors that may play a role in prediction differences, such as market conditions, economic policies, and other fundamental factors. Therefore, the research results are divided into two based on the gold price datasets from 2012 to 2023 and from 2020 to 2023. The testing results are based on the dataset from 2012 to 2023.